(untitled) (Scientific journal of the Fergana State University, 2024)
Looking at the literary sources that reflect the socio-political history of the peoples of the world, we can observe such problems as social inequality and injustice in the treatment of representatives of both genders. Family matters, domestic life, personal and social problems are expressed in the narratives and legends that reflect the attitude of our ancestors to social reality. Also, we can witness that the problems of family and household life are reflected in the background of social life in epics — folk epics, which have been handed down from ancestors to generations. Literary heroes who are committed to the benefit of a nation and the development of the nation, first of all, grow up in the family environment and endure the trials of everyday life. In this way, they will be prepared for the grandiose works and universal tasks that will be carried out in the future. In addition to raising children and family chores, women have also been active in the defense of the homeland and the well-being of the nation. Their various personal and social activities are widely and comprehensively reflected in folk oral poetic works, especially in epics. Thatʼs why there are many scenes in Uzbek folk oral poetry that give a certain idea about the lifestyle of our ancestors, in particular, the hard-working life of women. The article analyzes family values, national characteristics, factors of social development based on folk epics.